A method for preparing near-infrared remote-controlled self-powered electrospun nanofiber hydrogel scaffold
By combining piezoelectric PVDF electrospun film with thermally responsive dual network PNIPAM hydrogel and controlling charge generation using near-infrared radiation, the problem of external power dependence and piezoelectric materials in the prior art is solved, and the problem of difficulty in obtaining sufficient pressure is achieved. Remotely controlled charge generation promotes bone regeneration.
Patent Information
- Application Number
- CN202411756772.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-12-03
AI Technical Summary
The prior art has problems in clinical applications where external power dependence, difficulty in obtaining sufficient pressure to generate charges for piezoelectric materials, and pain caused by physical activity during fractures.
A new material system combining piezoelectric PVDF electrospun film with thermally responsive dual network PNIPAM hydrogel was designed to generate charges through near-infrared radiation control. The material is coated on barium titanate nanoparticles after polymerization of dopamine, and uses near-infrared radiation to cause deformation of the hydrogel, thereby causing the PVDF electrospun film to generate charge.
Remotely controlling the charge generation of piezoelectric materials without relying on external power supplies, solving the problem that the material is difficult to obtain sufficient pressure in the body, and reducing the pain in the patient during fractures.
Smart Images

Figure CN119236173B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomaterials, and in particular to a method for preparing a near-infrared remote-controlled self-powered electrospun nanofiber hydrogel scaffold. Background Art
[0002] In recent years, electrical stimulation has been shown to effectively promote the proliferation and differentiation of osteoblasts, providing a new strategy for bone regeneration and repair. Although various electrical stimulators have been commercialized for the treatment of fractures. However, the effects of external electrical stimulators are limited, and implanted devices rely on percutaneous wires and non-degradable batteries. These shortcomings limit the clinical application of electrical stimulation combined with tissue engineering. Therefore, self-powered implantable materials that can support biological processes and electrical stimulation functions without relying on external power sources have attracted increasing attention in tissue engineering and biomedicine, and show great potential for clinical transformation. Among them, piezoelectric materials including PVDF have the ability to generate electricity under external forces and have been widely used in bone tissue engineering, using body movement or external mechanical vibration to provide electrical stimulation and effectively promote bone growth. However, in clinical practice, plaster is usually used to fix the fracture area to prevent displacement, promote bone repair, and maintain the original alignment of the fracture. This method may hinder the piezoelectric material from obtaining sufficient pressure to generate the charge required for stimulation. In addition, additional physical activity during fracture may cause pain to patients. Therefore, a strategy that can remotely control the deformation of piezoelectric materials to generate charge is urgently needed.
[0003] At present, the main methods for charging implantable piezoelectric materials include polarization charging before implantation, magnetic field remote control, and ultrasonic remote control. When charging piezoelectric materials by polarization, the surface potential of the piezoelectric material will decrease after implantation in the body, making it difficult to maintain the physiological electrical microenvironment for a long time. The method of driving by magnetic field remote control requires the addition of ferromagnetic fillers to the material, and the continuous release of iron and cobalt ions inevitably puts the body at risk of biocompatibility. The method of driving by ultrasonic remote control needs to consider the damage of ultrasound to surrounding tissues. Even low doses of ultrasound are potential carcinogenic and teratogenic factors.
[0004] Based on this, the present invention provides a method for preparing a near-infrared remote-controlled self-powered electrospun nanofiber hydrogel scaffold. Summary of the invention
[0005] The purpose of the present invention is to design a new piezoelectric material system that combines a piezoelectric PVDF electrospun membrane with a thermally responsive double-network PNIPAM hydrogel, which can generate electric charges by controlling near-infrared (NIR) radiation, and polymerize dopamine with good photothermal properties and coat it on barium titanate nanoparticles.
[0006] When exposed to near-infrared radiation, the side of the PVDF electrospun membrane containing the particles will heat up. Since the entire PVDF electrospun membrane is wrapped by the thermally responsive PNIPAM hydrogel, the heated side will cause the hydrogel to shrink. The deformation of the hydrogel further causes the PVDF electrospun membrane to deform and generate electric charges, thereby realizing remote control of the piezoelectric properties of implantable piezoelectric materials.
[0007] The present invention provides a method for preparing a near-infrared remote-controlled self-powered electrospun nanofiber hydrogel scaffold, the steps comprising:
[0008] (1) Preparing electrospinning precursor solution: dissolving P(VDF-TrFE) and barium titanate nanoparticles in a mixed solution of N,N-dimethylformamide solution and acetone to obtain precursor solution 1; dissolving P(VDF-TrFE) and barium titanate nanoparticles coated with polydopamine in a mixed solution of N,N-dimethylformamide solution and acetone to obtain precursor solution 2;
[0009] (5) Preparation of P(VDF-TrFE) piezoelectric composite film: Precursor solution 1 and precursor solution 2 are placed in a syringe pump in sequence, and a double-layer piezoelectric composite film is prepared by a uniaxial electrospinning process;
[0010] (6) Preparing a hydrogel precursor solution: dissolving sodium alginate and anhydrous calcium chloride in deionized water, heating and stirring to obtain solution A; dissolving N-isopropylacrylamide and acrylamide in solution A to obtain solution B; dissolving ammonium persulfate in solution B to obtain solution C;
[0011] Preparation of a piezoelectric and thermal responsive double network hydrogel scaffold: The double-layer piezoelectric composite film is transferred to a glass sheet, and the solution C is dripped onto the double-layer piezoelectric composite film. After the solution C completely penetrates the composite film, it is covered with another glass sheet, placed in a culture dish, and left to stand overnight to obtain a piezoelectric and thermal responsive double network hydrogel scaffold.
[0012] Furthermore, the preparation method of the polydopamine-wrapped barium titanate nanoparticles includes: mixing the barium titanate nanoparticles and polydopamine, adding them to Tris HCl, magnetically stirring, collecting the solution into a centrifuge tube and centrifuging it after protecting it from light overnight, discarding the supernatant, washing the precipitate three times with deionized water and then drying it to obtain the polydopamine-wrapped barium titanate nanoparticles.
[0013] Furthermore, in step (1), the dosage ratio of P(VDF-TrFE), barium titanate nanoparticles, N,N-dimethylformamide solution and acetone is: (1-3) g: (1-2) g: (5-7) mL: (3-5) mL.
[0014] Furthermore, the conditions for electrospinning in step (2) are: voltage 10-20 kV, flow rate 0.04-0.06 ml / min, shaft speed 500-700 rpm, and electrospinning distance 10-20 cm.
[0015] Furthermore, in step (2), the electrospinning time of the precursor solution 1 and the precursor solution 2 is 3-5 h.
[0016] Furthermore, in the step (3), the dosage ratio of sodium alginate, anhydrous calcium chloride and deionized water is (1-3) g: (0.1-0.3) g: (80-120) mL.
[0017] Furthermore, in the step (3), the usage ratio of N-isopropylacrylamide, acrylamide and the solution A is (0.8-1.2) g: (0.4-0.6) g: (8-12) mL.
[0018] Furthermore, in step (3), the usage ratio of ammonium persulfate to solution B is (0.01-0.03) g: (8-12) mL.
[0019] Furthermore, the stirring temperature in step (3) is 50-70°C.
[0020] Furthermore, the dosage ratio of the barium titanate nanoparticles, polydopamine and Tris HCl is (1-3) g: (1-2) g: (40-60) mL, wherein the pH of Tris HCl is 8.5 and the concentration is 1M.
[0021] The beneficial effects of the present invention are:
[0022] (1) Combining piezoelectric PVDF electrospun membrane with thermoresponsive double-network N-isopropylacrylamide hydrogel can generate electric charge by near-infrared radiation control; since the entire PVDF electrospun membrane in the present invention is wrapped by thermoresponsive PNIPAM hydrogel, the heated side will cause the hydrogel to shrink, and the deformation of the hydrogel will further cause the deformation of the PVDF electrospun membrane. Therefore, near-infrared radiation can be used to remotely control the generation of electric charge after the hydrogel is implanted in the body. In the field of tissue engineering, near-infrared regulation can be used after implantation to maintain the electrical microenvironment required for bone defect repair for a long time, thereby promoting bone regeneration.
[0023] (2) Sodium alginate is introduced into the hydrogel system to form a double network structure and improve the mechanical properties. In the solution, sodium alginate and calcium ions interact to form a first network connected by strong ionic bonds. Subsequently, N-isopropylacrylamide and acrylamide monomers undergo free radical polymerization to form a secondary network through covalent bonds. When the double network hydrogel is stretched, the ionic bonds will break preferentially, dissipating energy and increasing the stress-bearing area, thereby protecting the covalent bonds. The construction of the double network protects the covalent bonds formed by N-isopropylacrylamide and acrylamide monomers, maintains the stability of the hydrogel, prevents the precipitation of N-isopropylacrylamide monomers, and greatly reduces the biological toxicity of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a physical picture of the hydrogel scaffold in Example 1 of the present invention;
[0025] Figure 2 This is a test diagram of the hydrogel scaffold in Example 1 of the present invention;
[0026] Figure 3 This is a test diagram of the hydrogel scaffold in Example 2 of the present invention;
[0027] Figure 4 This is a test diagram of the hydrogel scaffold in Example 3 of the present invention. DETAILED DESCRIPTION
[0028] The technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Example 1
[0030] This embodiment provides a method for preparing a near-infrared remote-controlled self-powered electrospun nanofiber hydrogel scaffold, the steps comprising:
[0031] (1) Preparation of barium titanate nanoparticles coated with polydopamine: 2 g of barium titanate nanoparticles and 1 g of polydopamine were mixed and added to 50 ml of Tris HCl (1 M, pH 8.5), and magnetically stirred at 500 rpm in a dark place overnight; the above solution was collected in a centrifuge tube and centrifuged to discard the supernatant; the precipitate was washed three times with deionized water and placed in an oven at 80°C to dry to obtain barium titanate nanoparticles coated with polydopamine;
[0032] (2) Preparation of electrospinning precursor solution: 2 g P(VDF-TrFE) and 1 g barium titanate nanoparticles were dissolved in a mixed solution of 6 ml N,N-dimethylformamide solution and 4 ml acetone to obtain precursor solution 1; 2 g P(VDF-TrFE) and 1 g barium titanate nanoparticles coated with polydopamine were dissolved in a mixed solution of 6 ml N,N-dimethylformamide solution and 4 ml acetone to obtain precursor solution 2;
[0033] (3) Preparation of P(VDF-TrFE) piezoelectric composite film by electrospinning: Precursor solution 1 was placed in a 20 ml syringe pump and prepared using a uniaxial electrospinning process. After 4 hours of electrospinning, the syringe pump of precursor solution 1 was removed and precursor solution 2 was placed in a 20 ml syringe pump and prepared using a uniaxial electrospinning process. After continuing electrospinning for 4 hours, a double-layer piezoelectric composite film was obtained. The electrospinning conditions were as follows: voltage 15 kV, flow rate 0.05 ml / min, shaft speed 600 rpm, and electrospinning distance 15 cm.
[0034] (4) Prepare hydrogel precursor solution: weigh 1.0 g sodium alginate and 0.2 g anhydrous calcium chloride and dissolve them in 100 ml deionized water, heat and stir at 60 °C to obtain solution A; weigh 1.0 g N-isopropylacrylamide and 0.5 g acrylamide and dissolve them in 20 ml of the above solution A to obtain solution B; weigh 0.02 g ammonium persulfate and dissolve it in solution B to obtain solution C;
[0035] (5) Preparation of a piezoelectric thermoresponsive double network hydrogel scaffold: The prepared double-layer piezoelectric composite film is transferred to a glass slide, and the solution C is dripped onto the double-layer piezoelectric composite film to allow the solution C to completely penetrate the composite film. Then, another glass slide is used to cover it, and the mixture is placed in a culture dish and allowed to stand overnight to obtain a piezoelectric thermoresponsive double network hydrogel scaffold.
[0036] Test example:
[0037] 1. Test method:
[0038] A general picture of the prepared piezoelectric thermal responsive double-network hydrogel scaffold was taken; after clamping it vertically to the horizontal plane, it was irradiated horizontally using an 808 nm wavelength near-infrared laser transmitter to observe the changes in the hydrogel.
[0039] 2. Results and Analysis
[0040] like Figure 1 As shown, the hydrogel is divided into two sides, brown and white, where the brown side is the barium titanate nanoparticle side wrapped by polydopamine. Figure 2 It was shown that the hydrogel scaffold would bend toward the side with polydopamine coating (brown side) regardless of irradiation from the brown side or the white side.
[0041] 3. Conclusion
[0042] Near-infrared radiation induces a thermal response on the polydopamine-coated side, causing the hydrogel to shrink.
[0043] Example 2
[0044] This embodiment provides a method for preparing a hydrogel scaffold, the steps comprising:
[0045] (1) Preparation of barium titanate nanoparticles coated with polydopamine: 2 g of barium titanate nanoparticles and 1 g of polydopamine were mixed and added to 50 ml of Tris HCl (1 M, pH 8.5), and magnetically stirred at 500 rpm in a dark place overnight; the above solution was collected in a centrifuge tube and centrifuged to discard the supernatant; the precipitate was washed three times with deionized water and placed in an oven at 80°C to dry to obtain barium titanate nanoparticles coated with polydopamine;
[0046] (2) Preparation of electrospinning precursor solution: Dissolve 2 g P(VDF-TrFE) and 1 g polydopamine-coated barium titanate nanoparticles in a mixed solution of 6 ml N,N-dimethylformamide solution and 4 ml acetone to obtain precursor solution 1; repeat this step to obtain precursor solution 2.
[0047] (3) Preparation of P(VDF-TrFE) piezoelectric composite film by electrospinning: Precursor solution 1 was placed in a 20 ml syringe pump and prepared using a uniaxial electrospinning process. After 4 hours of electrospinning, the syringe pump of precursor solution 1 was removed and precursor solution 2 was placed in a 20 ml syringe pump and prepared using a uniaxial electrospinning process. After continuing electrospinning for 4 hours, a double-layer piezoelectric composite film was obtained. The electrospinning conditions were as follows: voltage 15 kV, flow rate 0.05 ml / min, shaft speed 600 rpm, and electrospinning distance 15 cm.
[0048] (4) Prepare hydrogel precursor solution: weigh 1.0 g sodium alginate and 0.2 g anhydrous calcium chloride and dissolve them in 100 ml deionized water, heat and stir at 60 °C to obtain solution A; weigh 1.0 g N-isopropylacrylamide and 0.5 g acrylamide and dissolve them in 20 ml of the above solution A to obtain solution B; weigh 0.02 g ammonium persulfate and dissolve it in solution B to obtain solution C;
[0049] (5) Preparation of piezoelectric double-network hydrogel scaffold: The prepared double-layer piezoelectric composite film is transferred to a glass slide, and the solution C is dripped onto the double-layer piezoelectric composite film to allow the solution C to completely penetrate the composite film. Then, another glass slide is used to cover it, and the mixture is placed in a culture dish and allowed to stand overnight to obtain a piezoelectric double-network hydrogel scaffold.
[0050] like Figure 3As shown, the hydrogel scaffold prepared by spinning with PDA on both sides in this embodiment did not deform after testing.
[0051] Example 3
[0052] This embodiment provides a method for preparing a hydrogel scaffold, the steps comprising:
[0053] (1) Preparation of electrospinning precursor solution: 2 g P(VDF-TrFE) and 1 g barium titanate nanoparticles were dissolved in a mixed solution of 6 ml N,N-dimethylformamide solution and 4 ml acetone to obtain precursor solution 1; this step was repeated to obtain precursor solution 2;
[0054] (2) Preparation of P(VDF-TrFE) piezoelectric composite film by electrospinning: Precursor solution 1 was placed in a 20 ml syringe pump and prepared using a uniaxial electrospinning process. After 4 hours of electrospinning, the syringe pump of precursor solution 1 was removed and precursor solution 2 was placed in a 20 ml syringe pump and prepared using a uniaxial electrospinning process. After continuing electrospinning for 4 hours, a double-layer piezoelectric composite film was obtained. The electrospinning conditions were as follows: voltage 15 kV, flow rate 0.05 ml / min, shaft speed 600 rpm, and electrospinning distance 15 cm.
[0055] (3) Prepare hydrogel precursor solution: weigh 1.0 g sodium alginate and 0.2 g anhydrous calcium chloride and dissolve them in 100 ml deionized water, heat and stir at 60 °C to obtain solution A; weigh 1.0 g N-isopropylacrylamide and 0.5 g acrylamide and dissolve them in 20 ml of the above solution A to obtain solution B; weigh 0.02 g ammonium persulfate and dissolve it in solution B to obtain solution C;
[0056] (4) Preparation of a piezoelectric double-network hydrogel scaffold: The prepared double-layer piezoelectric composite film is transferred to a glass slide, and the solution C is dripped onto the double-layer piezoelectric composite film to allow the solution C to completely penetrate the composite film. Then, another glass slide is used to cover it, and the mixture is placed in a culture dish and allowed to stand overnight to obtain a piezoelectric double-network hydrogel scaffold.
[0057] like Figure 4 As shown, the hydrogel scaffold prepared by spinning without PDA on both sides in this embodiment also did not deform after testing.
[0058] Finally, it should be noted that the above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents. All technical solutions and improvements that do not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a near-infrared remote-controlled self-powered electrospun nanofiber hydrogel scaffold, characterized in that the steps include: (1) Preparing electrospinning precursor solution: dissolving P(VDF-TrFE) and barium titanate nanoparticles in a mixed solution of N,N-dimethylformamide solution and acetone to obtain precursor solution 1; dissolving P(VDF-TrFE) and barium titanate nanoparticles coated with polydopamine in a mixed solution of N,N-dimethylformamide solution and acetone to obtain precursor solution 2; (2) Preparation of P(VDF-TrFE) piezoelectric composite film: Precursor solution 1 and precursor solution 2 are placed in a syringe pump in sequence, and a double-layer piezoelectric composite film is prepared by a uniaxial electrospinning process; (3) preparing a hydrogel precursor solution: dissolving sodium alginate and anhydrous calcium chloride in deionized water, heating and stirring to obtain solution A; dissolving N-isopropylacrylamide and acrylamide in solution A to obtain solution B; dissolving ammonium persulfate in solution B to obtain solution C; (4) Preparation of a piezoelectric thermoresponsive double network hydrogel scaffold: The double-layer piezoelectric composite film is transferred to a glass slide, and the solution C is dripped onto the double-layer piezoelectric composite film. After the solution C completely permeates the composite film, another glass slide is used to cover it, and the composite film is placed in a culture dish and allowed to stand overnight to obtain a piezoelectric thermoresponsive double network hydrogel scaffold.
2. The method for preparing a near-infrared remote-controlled self-powered electrospun nanofiber hydrogel scaffold according to claim 1, characterized in that: The preparation method of the polydopamine-wrapped barium titanate nanoparticles comprises: mixing barium titanate nanoparticles and polydopamine, adding the mixture into Tris HCl, magnetically stirring, collecting the solution into a centrifuge tube and centrifuging it after keeping it away from light overnight, discarding the supernatant, washing the precipitate three times with deionized water and drying it to obtain the polydopamine-wrapped barium titanate nanoparticles.
3. The method for preparing a near-infrared remote-controlled self-powered electrospun nanofiber hydrogel scaffold according to claim 1, characterized in that: In the step (1), the dosage ratio of P(VDF-TrFE), barium titanate nanoparticles, N,N-dimethylformamide solution and acetone is: (1-3) g: (1-2) g: (5-7) mL: (3-5) mL.
4. The method for preparing a near-infrared remote-controlled self-powered electrospun nanofiber hydrogel scaffold according to claim 1, characterized in that: The conditions for electrospinning in step (2) are: voltage 10-20 kV, flow rate 0.04-0.06 ml / min, shaft speed 500-700 rpm, and electrospinning distance 10-20 cm.
5. The method for preparing a near-infrared remote-controlled self-powered electrospun nanofiber hydrogel scaffold according to claim 1, characterized in that: In the step (2), the electrospinning time of the precursor solution 1 and the precursor solution 2 is 3-5 h.
6. The method for preparing a near-infrared remote-controlled self-powered electrospun nanofiber hydrogel scaffold according to claim 1, characterized in that: In the step (3), the dosage ratio of sodium alginate, anhydrous calcium chloride and deionized water is (1-3) g: (0.1-0.3) g: (80-120) mL.
7. The method for preparing a near-infrared remote-controlled self-powered electrospun nanofiber hydrogel scaffold according to claim 1, characterized in that: In the step (3), the usage ratio of N-isopropylacrylamide, acrylamide and the solution A is (0.8-1.2) g: (0.4-0.6) g: (8-12) mL.
8. The method for preparing a near-infrared remote-controlled self-powered electrospun nanofiber hydrogel scaffold according to claim 1, characterized in that: In the step (3), the dosage ratio of ammonium persulfate to solution B is (0.01-0.03) g: (8-12) mL.
9. The method for preparing a near-infrared remote-controlled self-powered electrospun nanofiber hydrogel scaffold according to claim 1, characterized in that: The stirring temperature in step (3) is 50-70°C.
10. The method for preparing a near-infrared remote-controlled self-powered electrospun nanofiber hydrogel scaffold according to claim 2, characterized in that: The dosage ratio of the barium titanate nanoparticles, polydopamine and Tris HCl is (1-3) g: (1-2) g: (40-60) mL.
Citation Information
Patent Citations
Preparing method for infrared response high-strength hydrogel for cartilago articularis repair
CN105107019A
Intelligent response hydrogel for constructing 3D tissue engineering graft as well as preparation method and application of intelligent response hydrogel
CN112870449A